The mediating effect of subjective well-being in the relationship between social support and professional commitment among mainland Chinese kindergarten teachers - Chen, Shujuan; Luo, Yun; Mai, Zheyuan; Chen, Xiaojing; Shen, Taoyu (Frontiers in Psychology, 2022)
Kindergarten teachers’ professional commitment affects their emotional input and turnover intention, and it is affected by the spiritual and material factors of teachers’ families, kindergartens, and society. Therefore, this study aimed to investigate the mediating effect of the dimensions of subjective well-being in the relationship between social support and professional commitment. The study is grounded in human ecology theory and social exchange theory. We surveyed 778 kindergarten teachers from different educational systems in Guangdong Province in China. We used the “Appreciative Social Support” and “Subjective Well-being” Scales and the “Professional Commitment Questionnaire.” The results showed that the four variables of social support, positive affect, life satisfaction, and professional commitment of kindergarten teachers were significantly and positively correlated with each other: social support positively predicted positive affect and life satisfaction, positive affect and life satisfaction positively predicted professional commitment, and social support indirectly influenced professional commitment through the parallel and chain path of positive affect and life satisfaction. This represents a compound multiple mediating effects on professional commitment.